Cholesterol granuloma presenting as a mass obstructing the external ear canal - Nikolaidis, Vasilios (BioMed Central, 2010)
BACKGROUND: Cholesterol granuloma (CG) may involve the middle ear, the mastoid bone and the petrous apex. However, CG presenting as a mass obstructing the external ear canal (EEC) is relatively rare and it can be a diagnostic challenge. CASE PRESENTATION: We report a case of a CG occupying the mastoid antrum and presenting as a mass into the EEC. Temporal bone computerized tomography showed a soft tissue mass which eroded the posterior-superior bony wall of the EEC. On magnetic resonance imaging, the mass revealed a high signal on both T1 and T2-weighted images. The CG was removed by a mastoidectomy procedure and the histopathologic report confirmed the diagnosis of CG. A type III tympanoplasty was performed. CONCLUSIONS: The postoperative course was uneventful.